Levels of Wistar Calcium Serum (Rattus Norvegicus) in Human Adipose-Derived Mesenchymal Stem Cells (hADMSCs) and Chitosan Scaffold by Osteoinduction Examination - Destri Imania Destri (Journal of Stem Cell Research and Tissue Engineering, 2022)
Bone tissue reconstruction with extensive damage is one of the challenges for dentists because its healing process of bone tissue. Bone graft is the gold standard for bone repair. However, the use of bone graft has a limited amount of tissue produced. Tissue engineering is the latest method in terms of bone regeneration. Tissue engineering has three main components, first is stem cells that have self renewal ability and multineage differentiation, second is bioreactor / growth factor, and then scaffold. The combination of hADMSC and chitosan scaffold, is expected to trigger osteoinduction shown by osteogenic markers such as calcium levels. Purpose to prove osteoinduction in a combination of Human Adiposed Derived Mesenchymal Stem Cell (hADMSC) and chitosan scaffold using blood serum calcium levels. Methods: This study uses 12 treatment groups with each group having 4 samples. Groups 1 to 4 were the negative control group at 1st,3rd,7th, and 14th days which maxillary bone drilling only. While groups 5 to 8 were the positive control group at 1st,3rd,7th, and 14th days which were given chitosan scaffold. Groups 9 to 12 were treatment group at 1st,3rd,7th, and 14th days which were given hADMSC and chitosan scaffold. Blood collection is carried out in each group to check serum calcium levels. Result there were differences in calcium levels in blood serum in each group. Conclusion the application of hADMSC and chitosan scaffold caused a significant change in serum calcium levels on the 1st, 3rd, 7th and 14th days which meant that the combination of hADMSC and chitosan scaffold could trigger osteoinduction.